PENERAPAN TEMATIK NYANYIAN MANTAU KE DALAM BENTUK LAGU DUA BAGIAN “MANTAU” - Ana Dilla Putri (Melayu Arts and Performance Journal, 2021)
The art of Mantau is one of the traditional music that grows and delops in the area of Bangko Subdistrict, Merangin Regency, Jambi Province in the form of traditional singing or vocal performed by one singer. In addition to possessing vocal abilities, the singer Mantau must have to ability to deliver poems arranged in the form of poetry spontaneously according to local circumstances or events. In addition, there is a unique in Mantau art which is a characteristic of Mantau melodies that tend to uses mixolidyan modes material sung with rubato and ad libitum technique. The puspose of creating this composition is to demonstrate the composition of musical composition that are processed and developed in the orchestra format. The method used in the process of creating this musical composition is exploration, impovisation, experimentation, and formation.Keyword : Mantau; Mixolidyan modes; Composition; Orchetra.AbstrakKesenian Mantau merupakan salah satu kesenian tradisi yang tumbuh dan berkembang di daerah Kecamatan Bangko Kabupaten Merangin Provinsi Jambi yang berbentuk nyanyian atau vokal tradisional yang dibawakan oleh satu orang penyanyi. Selain mempunyai vokal yang mempuni, penyanyi Mantau mesti memiliki kemampuan dalam menyampaikan syair-syair lagu yang tersusun dalam bentuk pantun secara spontan sesuai dengan keadaan atau kejadian setempat. Selain itu, terdapat keunikan dalam kesenian Mantau yang mana karakteristik dari melodi Mantau yang cenderung memakai material mixolidya modes dinyanyikan dengan teknik rubato dan ad libitum. Tujuan dari penciptaan musik yang diolah dan dikembangkan dengan format orchestra. Metode yang digunakan dalam proses penciptaan komposisi musik ini yaitu eksplorasi, improvisasi atau eksperimen dan pembentukan.Kata Kunci: Mantau, Mixolidyan modes, Komposisi, Orkestra.